DOI: 10.31274/rtd-180813-12113
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of autumn growth and winter hardiness in alfalfa

Abstract: Alfalfa (Medicago sativa L.) has a broad geographic distribution, with some populations adapted to cold climates and others lacking cold tolerance. Although considerable research on winter hardiness in alfalfa has been conducted, much remains unknown about the mechanisms and genetic control of winter survival. We conducted two experiments designed to identify and quantify morphological, physiological, and biochemical traits associated with winter hardiness and to estimate the genetic relationship of these trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Winter hardiness was correlated (P < 0.01) to linoleic acid in orchardgrass (r 2 = 0.08) and (P < 0.05) in tall fescue to α-linolenic acid (r 2 = 0.03) (data not shown). This result is supported by Alarcón Zúñiga (2003), who compared FA concentrations and winter injury in roots of several alfalfa cultivars diff ering in winter hardiness. Samala et al (1998) reported that the winter-hardy bermudagrass cultivar Midiron had a higher percentage of α-linolenic acid after 21 d of cold treatment than the nontolerant cultivar U3.…”
Section: Fatty Acid Correlation To Phenotypic Traitsmentioning
confidence: 55%
See 3 more Smart Citations
“…Winter hardiness was correlated (P < 0.01) to linoleic acid in orchardgrass (r 2 = 0.08) and (P < 0.05) in tall fescue to α-linolenic acid (r 2 = 0.03) (data not shown). This result is supported by Alarcón Zúñiga (2003), who compared FA concentrations and winter injury in roots of several alfalfa cultivars diff ering in winter hardiness. Samala et al (1998) reported that the winter-hardy bermudagrass cultivar Midiron had a higher percentage of α-linolenic acid after 21 d of cold treatment than the nontolerant cultivar U3.…”
Section: Fatty Acid Correlation To Phenotypic Traitsmentioning
confidence: 55%
“…Therefore, it seems that an increase in the winter survivability, measured either by winter hardiness or fall dormancy has some basic impact on the FA concentrations even under nonfreezing conditions. This result is supported by Alarcón Zúñiga (2003), who compared FA concentrations and winter injury in roots of several alfalfa cultivars diff ering in winter hardiness. Cultivars with higher concentrations of linoleic, palmitic, and α-linolenic acid in autumn experienced less injury over winter.…”
Section: Fatty Acid Correlation To Phenotypic Traitsmentioning
confidence: 55%
See 2 more Smart Citations
“…Environments E3 and E4 were previously described by Alarcón- Zúñiga (2003). Briefly, field plots were established using the same population at the Agronomy and Agricultural Engineering Research Farm west of Ames, IA, on 1 June 2001 and on 15 May 2002.…”
Section: Phenotypic Data Collectionmentioning
confidence: 99%